Cross-setting Comparison of Risk Factors for Pressure Injuries Acquired in Post-Acute Care. (March 2023) - Barch, Daniel H.; Seibert, Julie Hayes; Kandilov, Amy; Bernacet, Amarilys; Deutsch, Anne; Wang, Xiao (Joyce); Scherer, Elissa; McMullen, Tara; Mandl, Stella; Levitt, Alan; Frank, Jennifer; Stephanopoulos, Cynthia; et al.
Abstract : GENERAL PURPOSE: To provide information on the association between risk factors and the development of new or worsened stage 2 to 4 pressure injuries (PIs) in patients in long-term care hospitals (LTCHs), inpatient rehabilitation facilities (IRFs), and skilled nursing facilities (SNFs). TARGET AUDIENCE: This continuing education activity is intended for physicians, physician assistants, nurse practitioners, and nurses with an interest in skin and wound care. LEARNING OBJECTIVES/OUTCOMES: After participating in this educational activity, the participant will: 1. Compare the unadjusted PI incidence in SNF, IRF, and LTCH populations. 2. Explain the extent to which the clinical risk factors of functional limitation (bed mobility), bowel incontinence, diabetes/peripheral vascular disease/peripheral arterial disease, and low body mass index are associated with new or worsened stage 2 to 4 PIs across the SNF, IRF, and LTCH populations. 3. Compare the incidence of new or worsened stage 2 to 4 PI development in SNF, IRF, and LTCH populations associated with high body mass index, urinary incontinence, dual urinary and bowel incontinence, and advanced age. ABSTRACT: OBJECTIVE: To compare the incidence of new or worsened pressure injuries (PIs) and associated risk factors for their development in inpatient post-acute care settings: long-term care hospitals (LTCHs), inpatient rehabilitation facilities (IRFs), and skilled nursing facilities (SNFs). METHODS: The authors investigated Medicare Part A SNF resident stays and LTCH patient stays that ended between October 1, 2016 and December 31, 2016 and IRF patient stays that ended between October 1, 2016 and March 31, 2017. They calculated the incidence of new or worsened PIs using the specifications of the National Quality Forum-endorsed PI quality measure #0678: Percent of Residents or Patients with Pressure Ulcers that are New or Worsened . RESULTS: The incidences of new or worsened stages 2 through 4 PIs varied across settings: 1.23% in SNFs, 1.56% in IRFs, and 3.07% in LTCHs. Seven risk factors were positively and consistently associated with new or worsened PIs across settings: limited bed mobility, bowel incontinence, low body mass index, diabetes/peripheral vascular disease/peripheral arterial disease, advanced age, urinary incontinence, and dual urinary and bowel incontinence. CONCLUSION: These findings provide empirical support for the alignment of risk factors for the PI quality measures across post-acute care settings.